Development of Android-Based Rhythmic Activity Learning Media on Physical Education in High School (Journal of Physical Education and Sports, 2018)
Rhythmic activity learning medium in High School can facilitate rhythmic activity learning for teachers and students. The present research aims to generate an android-based rhythmic activity learning medium and the effectiveness of the product. The developmental procedure used in this research including product analysis, initial product, expert validation, trial, product revision, final result, and effectiveness test. The instruments used questionnaire and interview. The subjects and study setting were High School teachers and students in Pekalongan Regency. The results of expert validation from material experts on the entire aspects were â€œexcellenceâ€ with the mean score was 4.42. The value of media experts on the product was â€œexcellenceâ€ with the mean score was 4.46. The trial for teacher and students were â€œexcellenceâ€ with the mean scores were 4.18 and 4.41, respectively. The entire means of product effectiveness test of android-based rhythmic activity learning were â€œexcellenceâ€ by 8%. It can be concluded that android-based rhythmic activity learning could facilitate learning process and be a learning source which was able to be used and utilised by teachers and students.